Fragmented legacies. Memories of agriculture and the railway in the transformation of Stacioni i Trenit in Tirana (Albania) - Stela Muçi; Franck Dorso (Territoire en Mouvement)
This article discusses heritagisation in Albania. It starts by situating the issue in the history of the country and the course taken by the city and the Stacioni i Trenit district. This district used to house the central station, until it was destroyed in 2013, as well as agricultural facilities which were dismantled after the fall of Communism in 1990. This site now forms a 25-hectare wasteland, characterized by a variety of informal uses, the incomplete reprivatisation of land, and a major urban transformation project. We explore how the legacies of agriculture and the railway in Stacioni i Trenit transpire in practices, how they are identified and used by the various protagonists, and to what extent the heritagization process may reveal social and spatial dynamics at work more broadly across Tirana and Albania today. Data presented in the text stems from a multidisciplinary research project conducted since 2018, combining urban planning, architecture, sociology, and anthropology.